Comparative pharmacokinetics of the main active components in normal and ulcerative colitis rats after oral administration of Zingiberis Rhizoma–Ginseng Radix et Rhizoma herb pair and its single herb extracts by LC–MS/MS - Wan, Yue; Dong, Zhiling; Li, Huifang; Yang, Lei; Li, Wenwen; Zhu, Ke; Jiang, Shu; Qian, Dawei; Duan, Jinao (Journal of separation science, 2022)
Zingiberis Rhizoma and Ginseng Radix et Rhizoma are usually used together for the treatment of ulcerative colitis in clinical practices. However, their compatibility mechanism remains unclear. In this study, a rapid and sensitive liquid chromatography with tandem mass spectrometry method was developed for simultaneous quantification of ginsenoside Re, ginsenoside Rg1, ginsenoside Rb1, and 6‐gingerol in rat plasma after oral administration of Zingiberis Rhizoma–Ginseng Radix et Rhizoma herb pair and its single herb extracts. The calibration curves exhibited good linearity, with correlation coefficients of more than 0.993. The precision deviations of intra‐ and interday analysis were within 10.66%, and accuracy error ranged from −12.74 to 11.56%. The average recoveries of analytes were higher than 76.60% and the matrix effects were minimal. Thus, the validated method was successfully applied to a pharmacokinetic study of four ingredients in normal and ulcerative colitis rat plasma. The results indicated that the pharmacokinetic parameters of four analytes in normal and model groups showed significant differences. The larger exposure (the mean AUC0‐t of ginsenoside Re, ginsenoside Rg1, ginsenoside Rb1, and 6‐gingerol were increased by 50.93, 141.90, 3.68, and 37.25%, respectively) and slower elimination (the CLz/F of ginsenoside Re, ginsenoside Rg1, and 6‐gingerol were decreased by 52.94, 83.64, and 32.18%, respectively) were observed in ulcerative colitis rats. Furthermore, compared with single herbs, the analytes in rat plasma after oral administration of combined extracts presented relatively high systemic exposure levels with AUC0‐t > 2000 h·ng/mL and Cmax > 200 ng/mL. Collectively, the differences of pharmacokinetic characteristics revealed the synergistic effect of Zingiberis Rhizoma–Ginseng Radix et Rhizoma herb pair, which provided a valuable and reliable basis for its clinical application in the treatment of ulcerative colitis.